Smooth versus Textured Implant Breast Reconstruction: Patient-Reported Outcomes and Complications. (8th September 2021) - Vorstenbosch, Joshua; McCarthy, Colleen M.; Shamsunder, Meghana G.; Polanco, Thais O.; Dabic, Stefan; Wiser, Itay; Matros, Evan; Dayan, Joseph; Disa, Joseph J.; Pusic, Andrea L.; Cavalli, Michele R.; Encarnacion, Elizabeth; et al.
Abstract : Background: The association between textured surface breast implants and breast implant-associated anaplastic large cell lymphoma has led to an increase in surgical procedures to exchange textured devices to smooth surface implants. Because patient satisfaction is an integral part of breast reconstruction, the purpose of this study was to compare patient-reported outcomes between smooth and textured implant recipients. Methods: Patients aged 18 years or older who underwent implant-based postmastectomy breast reconstruction with either smooth or textured devices from 2009 to 2017 and completed the BREAST-Q patient-reported outcome measure following reconstruction were included in this analysis. The primary outcomes of interest were mean and median BREAST-Q scores and postoperative complications. Results: Overall, 1077 patients were included—785 who underwent breast reconstruction with smooth implants and 292 who underwent breast reconstruction with textured implants. No statistical differences were observed between the textured and smooth implant groups for any of the BREAST-Q domain scores at any of the early (3-month) to late (2-year) postoperative time points. Smooth implant recipients reported significantly more rippling ( p = 0.003) than textured implant recipients. In contrast, textured implant recipients had a higher rate of cellulitis than smooth implant recipients ( p = 0.016). Conclusions: These data suggest that postoperative satisfaction with breasts or health-related quality of life following immediate postmastectomy implant-based breast reconstruction is likely independent of implant surface type. However, smooth breast implants may result in more rippling. The authors' findings represent an important aid in counseling patients who have questions about the risks and benefits of replacing their textured implants with smooth surface devices. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.